SOME MEASURES TO FORM SHAPE ICONS FOR 5-6 YEARS OLDS CHILDREN - Vũ Thị, Diệu Thuý; Đinh Thị, Hồng Loan; Bùi Hương, Giang (SCIENTIFIC JOURNAL OF TAN TRAO UNIVERSITY, 2021)
The article briefly introduces the characteristics of shape symbol formation of 5-6 year old children, thereby giving measures to from shape symbol formation for 5-6 year old children from the poin of view of child-centered education. These measures are built according to a logical structure, a clear sequence of instructions toi help preschool teachers apply in organnizing activities to teach 5-6 year old children to become familiar with math.